The Development Of Teaching Video Media Based On Tri Kaya Parisudha In Educational Psychology Courses - Okta Priantini, Dewa Ayu Made Manu (Journal of Education Technology, 2020)
This research aimed to implement learning in educational psychology courses that tend to be boring and have low learning outcomes. This research was a research and development (research and development). The research trial subjects were students from the PGSD Study Program. The data collected in this study were data from subject content expert tests, design expert tests, instructional media expert tests, and student trials. The data collection instrument was an evaluation sheet (questionnaire) for both expert testing and student testing. Data analysis used qualitative descriptive analysis and quantitative descriptive analysis. The results of the assessment of media products were carried out based on six aspects, namely: content aspects of the field of study / with the percentage of the achievement level of 88.05% with the title feasible; In terms of the learning design aspect, the percentage of achievement level was 84.65%, the predicate was feasible; in terms of the learning media aspect with the achievement level percentage of 87.00%, the predicate was feasible; In terms of the individual trial aspect, the percentage level of achievement of 91.55% predicates was very feasible; small group trial, with the percentage level of achievement of 93.40% predicate very feasible; and viewed from the aspect of field trials with the percentage level of achievement of 92.46% predicate very feasible. Thus, this instructional video media product had a good validity level and was suitable for the Educational Psychology course's learning process.